2011
DOI: 10.1038/ncb2386
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic targeting of Src promotes cancer cell survival following reduced FAK signalling

Abstract: Here we describe a mechanism that cancer cells use to survive when flux through the Src/FAK pathway is severely perturbed. Depletion of FAK, detachment of FAK-proficient cells or expression of non-phosphorylatable FAK proteins causes sequestration of active Src away from focal adhesions into intracellular puncta that co-stain with several autophagy regulators. Inhibition of autophagy results in restoration of active Src at peripheral adhesions, and this leads to cancer cell death. Autophagic targeting of activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
183
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(201 citation statements)
references
References 22 publications
18
183
0
Order By: Relevance
“…Taking these data together, we feel that future studies should clarify the molecular basis behind these observations. Present findings are consistent with an earlier report by Sandilands et al that Cbl is required for autophagic targeting of active c-Src in squamouse carcinoma cells (36), providing a confirmatory evidence that a similar molecular pathway is operational in normal epithelial cells. Because of technical challenges associated with manipulating primary cells, we have yet to investigate whether this function requires ubiquitin ligase activity of Cbl family proteins.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Taking these data together, we feel that future studies should clarify the molecular basis behind these observations. Present findings are consistent with an earlier report by Sandilands et al that Cbl is required for autophagic targeting of active c-Src in squamouse carcinoma cells (36), providing a confirmatory evidence that a similar molecular pathway is operational in normal epithelial cells. Because of technical challenges associated with manipulating primary cells, we have yet to investigate whether this function requires ubiquitin ligase activity of Cbl family proteins.…”
Section: Discussionsupporting
confidence: 94%
“…Sandilands et al previously reported that Cbl functions as a selective autophagy cargo receptor to protect FAK-deficient mouse squamous carcinoma cells from cell death caused by active Src turnover failure (36). Although their system differs from our present model in a number of aspects, colocalization of ProteoStat (+) aggregates with an autophagosome marker LC3, as well as the presence of active c-Src in detergent-insoluble fractions in our system, led us to ask whether the death of Cbl triple-deficient MECs was because of accumulation of active c-Src.…”
Section: Dasatinib Blocks Protein Aggregate Formation and Restores Ormentioning
confidence: 99%
“…Moreover, our work also emphasizes how FAK signaling can exert contrasting effects on autophagy and cell survival. Recent work from Sandilands and colleagues using a skin cancer model demonstrated that components of the autophagy pathway are intimately associated with focal adhesions, and that loss of FAK can trigger an apoptotic response, unless the active Src released upon FAK ablation is subject to autophagic targeting (49). This led to the suggestion that combining FAK and/or Src inhibitors with an autophagy inhibitor may reduce the viability of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Cbl has been identified as an autophagy receptor for the active, nonreceptor, membrane-associated tyrosine kinase Src (Sandilands et al, 2012). Increased Src activity promotes tumorigenesis but excessive Src signaling can be cytotoxic (Yeatman, 2004).…”
Section: Specialized Autophagy Receptorsmentioning
confidence: 99%